2017
DOI: 10.1038/ismej.2016.188
|View full text |Cite
|
Sign up to set email alerts
|

New insights into marine group III Euryarchaeota, from dark to light

Abstract: Marine Euryarchaeota remain among the least understood major components of marine microbial communities. Marine group II Euryarchaeota (MG-II) are more abundant in surface waters (4-20% of the total prokaryotic community), whereas marine group III Euryarchaeota (MG-III) are generally considered low-abundance members of deep mesopelagic and bathypelagic communities. Using genome assembly from direct metagenome reads and metagenomic fosmid clones, we have identified six novel MG-III genome sequence bins from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 105 publications
3
61
0
Order By: Relevance
“…All the assembled rhodopsin genes clustered with previously described groups indicating that surveys may have be saturating the 500 extant diversity of rhodopsins, at least in the oligotrophic ocean photic zone. Rhodopsin sequences clustered primarily by phylum, with the exception of euryarchaeal rhodopsins as previously reported (Iverson et al, 2012;Haro-Moreno et al, 2017). Within the proteorhodopsin cluster, we could clearly differentiate another bacterial cluster including only Bacteroidetes sequences (Figure 4a).…”
Section: Depth Stratification Of Rhodopsinssupporting
confidence: 80%
See 1 more Smart Citation
“…All the assembled rhodopsin genes clustered with previously described groups indicating that surveys may have be saturating the 500 extant diversity of rhodopsins, at least in the oligotrophic ocean photic zone. Rhodopsin sequences clustered primarily by phylum, with the exception of euryarchaeal rhodopsins as previously reported (Iverson et al, 2012;Haro-Moreno et al, 2017). Within the proteorhodopsin cluster, we could clearly differentiate another bacterial cluster including only Bacteroidetes sequences (Figure 4a).…”
Section: Depth Stratification Of Rhodopsinssupporting
confidence: 80%
“…Further analysis confirmed that all of them belonged to the same cluster ( Supplementary Figure 10), marine group II Euryarchaeota, known to be prevalent throughout the photic zone (Martin-Cuadrado et al, 2014). Whereas MED-G33 was closely 470 related to MG2-GG3 (Iverson et al, 2012), assembled from an estuary in the North Pacific, the remaining bins MED-G34 to MED-G38 were related with the recently described Thalassoarchaea Although we could not assign any contig to the marine group III Euryarchaeota, the recruitment of the previously described EUIII-Epi2 and EUIII-Epi6 (Haro-Moreno et al, 2017) showed that they were also present at the DCM. Ca.…”
Section: Archaeamentioning
confidence: 51%
“…Members of the MGII reside mainly in the marine photic zone although other ecotypes have been detected in deeper water columns (see Zhang, Xie, Martin-Cuadrado, & Rodriguez-Valera, 2015 for a review). MGIII archaea have been mainly detected in deep mesopelagic and bathypelagic, and most recently also in epipelagic waters, but their physiology is essentially unknown (Bano, Ruffin, Ransom, & Hollibaugh, 2004;Haro-Moreno, Rodriguez-Valera, López-García, Moreira, & Martin-Cuadrado, 2017; López-García, Moreira, López-López, & Rodriguez-Valera, 2001;Massana, DeLong, & Pedros-Alio, 2000), also because they remain uncultured. In addition, the presence of members of the archaeal superphylum DPANN in marine settings, mainly in microbial mats, sediments, plankton, and hydrothermal vents, is increasingly reported (Pachiadaki, Kallionaki, Dählmann, De Lange, & Kormas, 2011;Robertson, Spear, Harris, & Pace, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While MGII are more abundant in surface waters (Fuhrman and Davis, 1997;Massana et al, 2000;L opez-García et al, 2001;Mincer et al, 2007) and were also found in deep-sea water (Deschamps et al, 2014;Li et al, 2015;Liu et al, 2017), marine Thaumarchaeota are more abundant in meso-and bathypelagic waters (Karner et al, 2001;Herndl et al, 2005;Mincer et al, 2007;Teira et al, 2008;Varela et al, 2008). MGIII are generally considered to be more restricted to deeper waters (Massana et al, 2000;Galand et al, 2009) and, to a lesser extent, the photic zone (Haro-Moreno et al, 2017). Two major MGII groups, MGIIa and MGIIb , have been identified by their 16S rRNA gene (Massana et al, 2000;Martin-Cuadrado et al, 2008).…”
Section: Introductionmentioning
confidence: 99%